The Role of Enjoyment in Chatbot Usage for Customer Service - Amelia Amelia; Fathul Khaira; Rizky Kinenara Darussalam (Value : Jurnal Manajemen dan Akuntansi, 2026)
Integrating chatbots into customer service has become increasingly important as organisations seek to deliver efficient and engaging interactions. While prior studies have largely emphasised functional aspects, the role of emotional factors, particularly enjoyment, remains underexplored. This study examines the mediating role of enjoyment in the relationship between perceived usefulness, perceived ease of use, anthropomorphism, and chatbot usage. Data were collected from 368 Indonesian consumers with prior chatbot experience and analyzed using Structural Equation Modeling (SEM) with AMOS 26. The results show that perceived ease of use significantly enhances enjoyment, which in turn influences chatbot usage. Perceived usefulness directly affects chatbot usage but does not significantly influence enjoyment, while anthropomorphism has no significant effect on either enjoyment or usage. These findings suggest that emotional engagement in customer service is primarily driven by interaction simlicity rather than human-like chattbot characteristics, highlighting the limited role of anthropomorphism in efficiency-oriented service contexts.